KAJIAN KONSEP INKLUSIVITAS PADA INTERIOR STASIUN LRT BEKASI BARAT BAGI PENUMPANG BERKEBUTUHAN KHUSUS: STUDY OF THE INCLUSIVITY CONCEPTS IN THE INTERIOR OF BEKASI BARAT LRT STATION FOR PASSENGERS WITH SPECIAL NEEDS - Yuni Ferida; Cama Juli Rianingrum; Krishna Hutama (Jurnal Seni dan Reka Rancang: Jurnal Ilmiah Magister Desain, 2026)
Study of The Inclusivity Concepts In The Interior Of Bekasi Barat LRT Station For Passengers with Special Needs. The provision of LRT (Light Rail Transit) transportation modes in Jabodebek (Jakarta-Bogor-Depok-Bekasi) is in line with one of the SDGs (Sustainable Development Goals) goals outlined by Bappenas in reflecting inclusiveness and sustainability, namely Industry, Innovation and Infrastructure through the development of various public facilities, one of which is in the field of transportation, starting from the construction of roads, sea highways, airports, ports, as well as increasing the types of public transportation modes that can be accessed by various groups. However, in reality, the provision of transportation modes has not been fully able to facilitate the needs of passengers with special needs, such as people with disabilities and the elderly. This problem arises from a lack of attention to inclusiveness aspects in public spaces because the existing design is not in accordance with the universal design that has been implemented internationally. The research uses qualitative methods and through direct observation and theoretical studies in previous research. The aim of this research is to discuss how the concept of inclusivity is applied to the interior of the West Bekasi LRT station for passengers with special needs. The results of this research are that some of the interior facilities at the West Bekasi LRT Station almost fulfill the concept of Inclusivity which refers to Universal Design principles, but still need further evaluation.